Intermediates in extrachromosomal homologous recombination in Xenopus laevis oocytes: characterization by electron microscopy. - Pont-Kingdon, G (1993)
Several molecular mechanisms have been proposed to account for nonconservative homologous recombination. This type of recombination is particularly efficient in Xenopus oocytes when appropriate DNA substrates are injected. To distinguish between possible models, we have investigated recombination intermediates from oocytes by direct observation in the electron microscope. Partially recombined DNA was crosslinked with a psoralen derivative after incubation in oocytes to limit the branch migration that might occur during recovery procedures and alter the structures that were initially present. Branched structures, which we interpret as intermediates, represented approximately 10% of the DNA recovered and were readily analyzed. We did not observe any structures with internal loops predicted by invasion mechanisms. The majority of intermediates had one or two single-stranded branches on product-sized molecules, as predicted for incomplete junctions in the resection-annealing mechanism. Detailed length measurements confirmed the expectations of that model. When recovered DNA was not crosslinked, or when annealed junctions were prepared in vitro, we saw branched structures that indicated the occurrence of extensive branch migration. Comparison with the crosslinked sample confirmed the effectiveness of the crosslinking in preserving structures created in the oocytes. Our results strongly support a resection-annealing mechanism of recombination in oocytes.